ASSOCIATION AMONG MATHEMATICAL CRITICAL THINKING SKILL, COMMUNICATION, AND CURIOSITY ATTITUDE AS THE IMPACT OF PROBLEM-BASED LEARNING AND COGNITIVE CONFLICT STRATEGY (PBLCCS) IN NUMBER THEORY COURSE - Zetriuslita Zetriuslita; Wahyudin Wahyudin; Jarnawi Afgani Dahlan (Jurnal Infinity, 2018)
This research aims to find out the association amongMathematical Critical Thinking (MCT) ability, Mathematical Communication, and Mathematical Curiosity Attitude (MCA) as the impact of applying Problem-Based Learning Cognitive Conflict Strategy(PBLCCS) in Number Theory course. The research method is correlative study. The instruments include a test for mathematical critical thinking skill and communication, and questionnaire to obtain the scores of mathematical curiosity attitude. The findings show that: 1) there is no association between critical thinking skill and mathematical curiosity attitude as the impact of applying problem-based learning cognitive conflict strategy, 2) there is no association between mathematical communication and curiosity attitude as the impact of applying problem-based learning and cognitive conflict strategy, and 3) the impact of applying problem-based learning cognitive conflict strategy is more influential in developing critical thinkingskillthan communication skill and curiosity.